Improving The Marketing Performance Of District Umkm. Banyumas Through Ambidexterity: A Social Network Theory Approach - Saripermanik Budayanti; Weni Novandari; Refius Pradipta Setyanto (Citakonsultindo, 2024)
The ability to build social networks is important for MSMEs because social networks can provide opportunities for MSMEs to gain new customers, resources and market opportunities, which are important for their survival and growth, especially in rapidly changing markets. The aim of this research is to explore the Ambidexterity capabilities of MSMEs in Banyumas, with a focus on social network theory. Social networks are essential in providing resources, information, and support, which in turn influences the balance between exploration and exploitation activities in organizations. The number of samples in this study was 131 respondents from MSME actors and was analyzed using SmartPLS. The results of this research are that Strong Ties has a positive effect on Ambidexterity in Banyumas MSMEs. Weak Ties has a positive effect on Ambidexterity in Banyumas MSMEs. Strong Ties has a positive effect on Marketing Performance in Banyumas MSMEs. Weak Ties has a positive effect on Marketing Performance in Banyumas MSMEs and Ambidexterity has a positive effect on marketing performance.